Edible coatings and films to improve food quality - Baldwin, Elizabeth A.; Hagenmaier, Robert D.; Bai, Jinhe (CRC Press, 2012)
"Many interesting and exciting developments have occurred since the publication of the first edition in 1994. These developments result from the ever-increasing quality of coatings research, and make it timely to prepare this updated and completely revised 2nd edition, designed for the benefit of all involved in buying, selling, regulating, developing or using coatings to improve the quality and safety of foods. This book is a study of the coatings, films, wraps and surface treatments used for foods. Specifically, it covers coating ingredients and additives (Chapters 2, 3, 4 & 6), their permeability properties (Chapter 5), coatings for specific applications (Chapters 7, 8, 9 &12), the technology of coatings (Chapters 10 & 11), and regulatory aspects (Chapter 13). But of course the world of coatings could not be so neatly divided so some overlap between chapters in inevitable and desirable. For example, in the discussion of a coating made with a certain ingredient, the author might include information on additives used or allowed, and/or how the coating was applied, and/or what foods it is best used for, and so on. Therefore, in researching any topic it is best to cross-search other chapters"--